Genetics in palliative care: too much to ask?. (2nd May 2019) - Jacobs, Chris; White, Stephanie; Phillips, Jane
Abstract : People with an inherited condition who receive palliative care may be missing out on the opportunity to store a DNA sample for future use by their families and offspring. A DNA sample from a family member affected with an inherited condition can help at-risk relatives to access accurate risk assessment and, where relevant, enhanced surveillance and risk-reducing measures. As genetic and genomic testing becomes increasingly important in all aspects of healthcare, health professionals specialising in palliative care will be asked to communicate about family history risk and testing. This article highlights the importance of discussing genetics and genomics issues for people receiving palliative care, their families and the health professionals caring for them.